Facilitating Arabic Language Acquisition through STEM-Literacy and Life Skills-Based Digital Learning Resources for Quran Memorizers in Pesantren - Moh. Fery Fauzi; Nurul Murtadho; Laily Maziyah; Moh. Fauzan; Irma Anindiati; Auqi Lu’lu In Nada (Izdihar)
This research aimed to develop and evaluate the effectiveness of a STEM-literacy-lifeskills-based multimedia e-book (me-book) in facilitating Quranic comprehension through Arabic language learning in pesantren. The study employed a research and development (R&D) method, which included needs analysis, design, development, and evaluation stages. The effectiveness of the me-book was assessed through expert validation, trials with a target group of 90 students who memorize the Quran at PPTQ Al-Muanawiyah in Jombang, East Java, and an impact analysis on Arabic learning outcomes. The findings indicated that the me-book significantly enhances students’ engagement, comprehension, and retention of Arabic, ultimately supporting their ability to understand Quranic texts. Students’ perspectives further highlight the me-book’s role in making Arabic learning more structured and accessible, without undermining traditional pedagogical values. In conclusion, the STEM-literacy-lifeskills-based me-book serves as an effective instructional tool for pesantren students, bridging the gap between classical Arabic studies and contemporary educational methodologies to deepen their understanding of the Quran.